In Vitro Activity of the Ketolide ABT-773 - Barry, Arthur L. (American Society for Microbiology, 2001)
The in vitro activities of ABT-773, azithromycin, erythromycin, and clindamycin were compared by testing 1,223 clinical isolates selected to represent different species and phenotypes. ABT-773 was particularly potent against staphylococci (the MIC at which 90% of the strains tested were inhibited [MIC(90)] was ≤0.06 μg/ml), including all strains that were macrolide resistant but clindamycin susceptible. Streptococcus pneumoniae and other streptococci were inhibited by low concentrations of ABT-773, and that included most erythromycin-resistant strains. Against Haemophilus influenzae, ABT-773 and azithromycin were similar in their antibacterial potency (MIC(90), 4.0 and 2.0 μg/ml, respectively).